Adaptive real-time update dissemination in distributed virtual simulation environments - Chen, F.; Kalogeraki, V. (Eighth IEEE International Symposium on Object-Oriented Real-Time Distributed Computing (ISORC'05), 2005)
In this work we propose and evaluate a framework for efficient and real-time dissemination of dynamic data in distributed simulation virtual environments in a scalable fashion. A peer-to-peer overlay is used to create self-organizing groups of participants. Filters that combine application-level knowledge are utilized to control the message propagations and minimize the end-to-end delays. Our approach enables nodes to trade-off processing overhead for consistency precision. Our simulation results illustrate that our techniques meet the consistency requirements of the participants, while minimizing the data transmissions and the message delays.